Pengembangan Model Web Interaktif Dalam Mendukung Aktivitas Pariwisata Di Kota Batam - Amrizal Amrizal; Rika Harman (Prosiding, 2023)
Along with the decline in the covid pandemic in the city of Batam, the government has reopened the tourism faucet to the Batam area. The growth of tourist visits from month to month has increased. However, when compared to the level of tourist arrivals to Batam in the year before the Covid pandemic, it was very much different. Even though the government has improved tourism supporting infrastructure, service levels, better security conditions, the growth of visits has not met expectations. There is one aspect that needs to be developed, namely the aspect of information technology as a communication mouthpiece, travel guide and as an assistant in tourism travel. Information technology is able to solve existing problems in tourism activities in Batam City. For this reason, it is necessary to develop an integrated tourism portal between visitors, tour service providers consisting of the government, the private sector as tourism business managers in the city of Batam and other interested parties. The development of tourism portals is still individual in nature which is still not effective for visitors, because every visitor who needs information and tourism services must open various websites. For this reason, it is necessary to have an interactive web portal that is integrated from various aspects of needs and is expected to become a communicator from stakeholders in the Batam city tourism sector, and is also able to provide precise information on various types of activities in Batam City.